2014
DOI: 10.1021/jp501318p
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Hydroxyl Groups on Zinc Adsorption Characteristics on α-Al2O3(0001) Surfaces: First-Principles Study

Abstract: Adhesion at zinc/alumina interface is a key issue in the field of steelmaking industry, where selective Al oxidation, followed by surface segregation of alumina islands, efficiently impedes wetting of anticorrosive Zn coating on the high strength steel grades. Relying on ab initio total energy calculations, we have examined adsorption of Zn adatoms on different terminations of α-Al2O3(0001) surface under both vacuum conditions and in the presence of surface hydroxyls. Surface configurations with strongly bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 81 publications
6
56
0
Order By: Relevance
“…This comparison reveals a thermodynamic bias for an exchange between surface hydrogen and zinc atoms present under a wide span of oxygen-moderate and -rich environments. We recall that a similar trend has already been reported for Zn adsorbates at the hydroxylated α-alumina terminations, 32 for which the activated character of the hydrogen-zinc exchange has been explicitly demonstrated by both experiment and first principles calculations. 27 More importantly, all H-lean interface configurations present in the stability diagram Fig.…”
Section: Zinc/β -Cristobalite Interaction At Dehydrogenated Inter-supporting
confidence: 83%
See 1 more Smart Citation
“…This comparison reveals a thermodynamic bias for an exchange between surface hydrogen and zinc atoms present under a wide span of oxygen-moderate and -rich environments. We recall that a similar trend has already been reported for Zn adsorbates at the hydroxylated α-alumina terminations, 32 for which the activated character of the hydrogen-zinc exchange has been explicitly demonstrated by both experiment and first principles calculations. 27 More importantly, all H-lean interface configurations present in the stability diagram Fig.…”
Section: Zinc/β -Cristobalite Interaction At Dehydrogenated Inter-supporting
confidence: 83%
“…Surface pre-hydroxylation may be a promising way to achieve this. Moreover, it has been shown that reaction of metal adatoms with surface OH groups on prehydroxylated alumina results in a formation of strongly bound oxidized species, [28][29][30][31][32] and leads to a substantial improvement of zinc adhesion. 33 .…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of zinc/silica interactions under different thermodya CNRS, Institut des Nanosciences de Paris, UMR 7588, F-75005 Paris, France. Fax: ; +33 (0)1 44 27 39 82 Tel: +33 (0)1 44 27 46 17; E-mail: Jacek. Goniakowski@insp namic conditions will help to obtain a more precise understanding of the microscopic mechanisms responsible for the interfacial strength and to define appropriate process parameters promoting the adhesion of zinc coating on Si alloyed grades.…”
Section: Introductionmentioning
confidence: 99%
“…These water molecules then lead to the gradual decomposition of MAPbI 3 into MAI and PbI 2 . In addition, hydroxyl groups decompose the perovskite into PbI 2 , CH 3 NH 2 , I, and H 2 O . The generated water would further accelerate the decomposition process.…”
mentioning
confidence: 99%
“…[42,43] In addition, hydroxyl groups decompose the perovskite into PbI 2 , CH 3 NH 2 , I, and H 2 O. [44,45] The generated water would further accelerate the decomposition process. Equations (1) and (2) show possible degradation reactions for W-NiO x [40,46] :…”
mentioning
confidence: 99%